2021
DOI: 10.3389/fimmu.2021.704309
|View full text |Cite
|
Sign up to set email alerts
|

Differential CD147 Functional Epitopes on Distinct Leukocyte Subsets

Abstract: CD147, a member of the immunoglobulin (Ig) superfamily, is widely expressed in several cell types. CD147 molecules have multiple cellular functions, such as migration, adhesion, invasion, energy metabolism and T cell activation. In particular, recent studies have demonstrated the potential application of CD147 as an effective therapeutic target for cancer, as well as autoimmune and inflammatory diseases. In this study, we elucidated the functional epitopes on CD147 extracellular domains in T cell regulation us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This discrepancy was not surprising and could be due to the methods and subjects of the different studies. The interferon-γ release assay (IGRA) was employed in previous studies, [ 24 , 56 ] while intracellular IFN-γ expression in CD4 and CD8 T cells [ 57 ] was evaluated in the present study. Through the intracellular cytokine assay, the numbers of IFN-γ-producing CD4 and CD8 T cells could be directly monitored upon stimulation with S peptide pools.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy was not surprising and could be due to the methods and subjects of the different studies. The interferon-γ release assay (IGRA) was employed in previous studies, [ 24 , 56 ] while intracellular IFN-γ expression in CD4 and CD8 T cells [ 57 ] was evaluated in the present study. Through the intracellular cytokine assay, the numbers of IFN-γ-producing CD4 and CD8 T cells could be directly monitored upon stimulation with S peptide pools.…”
Section: Discussionmentioning
confidence: 99%
“…Hurdle analysis of quiescent naïve CD4 T cells identified 31 DEGs; following Immune Education and CLP versus CLP alone, expression in 24 was upregulated while expression in 7 was downregulated. Among the affected genes in the Immune-Educated CLP mice was Bsg (upregulated 2.29 fold, P <0.001), whose encoded protein basigin/CD147 has been shown to play a role in T cell activation and T reg differentiation, and because of this it has been studied as a potential therapeutic target for inflammatory diseases ( 82 , 83 ). There was also upregulation of Cdc42 (upregulated 2.25 fold, P <0.001), whose encoded protein (a Rho family GTPase) has been shown to play an essential role in actin polymerization for TCR clustering, Th1 differentiation, and memory cell survival in naïve CD4 T cells ( 84 ).…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we showed that the frequency of monocytes expressing the adhesion molecules CD147 and CD162 was diminished in pregnant women in response to TLR7/TLR8 stimulation. CD147, commonly termed Basigin, is a membrane receptor and member of the immunoglobulin superfamily that participates in cellular functions including migration and adhesion [ 77 80 ]. Similarly, CD162, or P-selectin glycoprotein ligand-1 (PSGL-1), acts as a ligand for selectins and is also a key player in leukocyte migration/adhesion [ 81 83 ].…”
Section: Discussionmentioning
confidence: 99%